One night gone : a novel - Laskowski, Tara (Graydon House, 2022)
One sultry summer, Maureen Haddaway arrives in the wealthy town of Opal Beach to start her life anew--to achieve her destiny. There, she finds herself lured by the promise of friendship, love, starry skies, and wild parties. But Maureen's new life just might be too good to be true, and before the summer is up, she vanishes. Decades later, when Allison Simpson is offered the opportunity to house-sit in Opal Beach during the off-season, it seems like the perfect chance to begin fresh after a messy divorce. But when she becomes drawn into the mysterious disappearance of a girl thirty years before, Allison realizes the gorgeous homes of Opal Beach hide dark secrets. And the truth of that long-ago summer is not even the most shocking part of all...